DETERMINATION OF BIOACTIVE CHEMICALS AND ANTIOXIDANT CAPACITY IN DIFFERENT PLANT PARTS OF CORIANDER (CORIANDRUM SATIVUM L.) - F. Ergün (Journal of Animal and Plant Sciences, 2022)
Substances with antioxidant activity protect the metabolism against oxidative damage caused by free radical molecules. The most important sources of these substances are herbal natural nutrients. Coriander (Coriandrum sativum L.) is a plant used both as a nutrient and as a medicine. Leaf, stem and seed parts of the plant are widely used as individual flavors. In this study, total phenolic and flavonoid content of hexane and methanol extracts obtained from leaf, stem and seeds of Coriander (C. sativum) plant were determined. The amount of phenolic substance was determined as 250 mg GAE / mL in the highest hexane seed extract and the lowest amount as 50 mg GAE / mL in methanol stem extract. The flavonoid substance was obtained in the highest hexane leaf extract with 535.71 µg QE/mL and the lowest in the hexane seed extract with 20.408 µg QE/mL. Although total phenolic and flavonoid content differed in leaf, stem and seed extracts, it was found to be higher in hexane extracts compared to the methanol extracts. In addition, IC50 values of both extracts were calculated using DPPH· radical removal activity method, which is among the antioxidant determination methods. Although the amount of phenolic and flavonoid content of methanol extract of coriander plant was low, DPPH· radical removal activity was found to be higher. It is considered that dietary incorporation of fresh leaf and seed parts of the coriander plant, whose phenolic substance and antioxidant capacity have been determined, might be significant with respect to the partial provision of the antioxidants needed by the organism.
Keywords: Coriander; Phenolic substance; Flavonoid substance; Antioxidant; DPPH